Functional Regulation of Macrophage Phenotypes by MicroRNAs in Inflammatory Arthritis - Niu, Xiaoling; Schulert, Grant S. (Frontiers in Immunology, 2019)
Inflammatory arthritis (including rheumatoid arthritis (RA) and juvenile idiopathic arthritis (JIA) exhibit the shared feature of changes in activation and polarization of circulating monocytes and tissue macrophages. Numerous microRNAs (miRs) have been found to have key functions in regulating inflammation and macrophage polarization. Although there is increasing interest in the roles of miRs in both RA and JIA, less is known regarding how miRs relate to functional properties of immune cells, including monocytes and macrophages. Interestingly, miRs can function both to promote inflammatory phenotypes and pro-inflammatory polarization, as well as through negative-feedback loops to limit inflammation. Here, we review the functional roles of several miRs in macrophages in inflammatory arthritis, with a particular focus on vivo effects of miR alteration in experimental arthritis. We also consider how current efforts to target miRs clinically could modify functional monocyte and macrophage polarization in vivo, and serve as novel therapies for diseases such as RA and JIA.